2021
DOI: 10.3390/foods10030534
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis Development and Aortic Contractility in Hypercholesterolemic Rabbits Supplemented with Two Different Flaxseed Varieties

Abstract: Alpha-linolenic acid (ALA) is widely regarded as the main beneficial component of flax for the prevention of cardiovascular disease. We evaluated the effect of the transgenic flaxseed W86—which is rich in ALA—on the lipid profile, atherosclerosis progression, and vascular reactivity in hypercholesterolemic rabbits compared to the parental cultivar Linola with a very low ALA content. Rabbits were fed a basal diet (control) or a basal diet supplemented with 1% cholesterol, 1% cholesterol and 10% flaxseed W86, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…This species can efficiently transform the residues of agricultural nature into a product of high nutritional-biological value meat [81]. Regarding the global sustainability in agriculture, agri-food by-products can be added to a variety of foods to increase their bioactive profile, fiber content, and antioxidant capacity [82][83][84][85] while maintaining good sensory acceptability, with applicability for rabbit meat, eventually for ready to eat products, like sausages, etc.…”
Section: Recommendation Of Rabbit Breeding and Meat Consumptionmentioning
confidence: 99%
“…This species can efficiently transform the residues of agricultural nature into a product of high nutritional-biological value meat [81]. Regarding the global sustainability in agriculture, agri-food by-products can be added to a variety of foods to increase their bioactive profile, fiber content, and antioxidant capacity [82][83][84][85] while maintaining good sensory acceptability, with applicability for rabbit meat, eventually for ready to eat products, like sausages, etc.…”
Section: Recommendation Of Rabbit Breeding and Meat Consumptionmentioning
confidence: 99%
“…In vivo and in vitro studies revealed the antioxidant activity of the SDG in flaxseed (Kezimana et al, 2018). Flaxseed therapy has been shown to slow the progression of atherosclerosis because of its lignan concentration and the antioxidant impact of SDG (Parikh and Pierce, 2019;Bujok et al, 2021;AlRamadneh et al, 2022).When rats with streptozotocin-induced diabetes were given SDG, there was a considerable reduction in glucose and lipid concentrationsand an improvement in insulin levelswhichreduces the chance of developing diabetes (Prasad et al, 2000;Draganescu et al, 2021). SDG is effective against inflammation, lowering reactive oxygen species levels and decreasing apoptosis.…”
Section: Introductionmentioning
confidence: 99%